2010
DOI: 10.1111/j.1471-4159.2009.06454.x
|View full text |Cite
|
Sign up to set email alerts
|

The PDZ domain protein CAL interacts with mGluR5a and modulates receptor expression

Abstract: 1These authors contributed equally to this study.Abbreviations used: CAL, CFTR-associated ligand; CFTR, cystic fibrosis transmembrane conductance regulator; CT, carboxyl-terminus; ER, endoplasmic reticulum; GST, glutathione-S-transferase; HA, hemagglutinin; His, hexahistidinetagged; mGluR, metabotropic glutamate receptor; NHERF-2, Na + /H + exchanger regulatory factor-2; PDZ, PSD95/Discslarge/ZO1homology; SDS-PAGE, sodium dodecyl sulfatepolyacrylamide gel electrophoresis; siRNA, small interfering RNA. Abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
1
24
1
Order By: Relevance
“…Previous studies with the CFTR have shown that PIST may target an associated membrane protein for lysosomal degradation (14,15). However, PIST does not appear to induce degradation of its associated G-protein-coupled receptors (6,9). In fact we report here that PIST stabilizes the ␤1 receptor and prevents postendocytic lysosomal degradation.…”
Section: Sorting Of ␤1-adrenergic Receptors By Pist/gopccontrasting
confidence: 43%
See 2 more Smart Citations
“…Previous studies with the CFTR have shown that PIST may target an associated membrane protein for lysosomal degradation (14,15). However, PIST does not appear to induce degradation of its associated G-protein-coupled receptors (6,9). In fact we report here that PIST stabilizes the ␤1 receptor and prevents postendocytic lysosomal degradation.…”
Section: Sorting Of ␤1-adrenergic Receptors By Pist/gopccontrasting
confidence: 43%
“…Whereas several receptors are sorted into a lysosomal, degradative pathway, others may be subject to recycling to the plasma membrane to allow for a new round of receptor activation and signaling. C-terminal PSD-95/discs large/ZO-1 (PDZ) ligand motifs, which enable selected receptors to bind to PDZ domain-containing proteins, have been established as important determinants for recycling (4) or degradation (6). Whereas some PDZ domain proteins serve as scaffolds for GPCR-associated signaling complexes at the plasma membrane (7,8), it is now becoming clear that receptors are handed over to other PDZ domain proteins during their passage through intracellular compartments (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GST pull-down assays and western blotting were performed as described previously (28). Antibody to NHERF1 was purchased from Becton Dickinson Company (Franklin Lake, NJ, USA), Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as an internal control (Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, CAL colocalizes with mGluR1a following agonist activation, and its overexpression decreases mGluR1a-stimulated ERK signaling (Zhang et al, 2008b). CAL is suggested to regulate mGluR5a function by increasing the expression of the receptor by a mechanism that involves the inhibition of mGluR5a ubiquitination (Cheng et al, 2010). Taken together, it appears CAL could have a regulatory role over the subcellular localization of a subset of GPCRs, perhaps by contributing to the post-translational modification of nascent and mature proteins that ultimately influence the sorting and trafficking fate.…”
Section: Pdz Proteins That Regulate Golgi Traffickingmentioning
confidence: 99%